Caracterização molecular e avaliação prognóstica de biomarcadores em linfoma difuso de grandes células b - Neves Filho, Eduardo Henrique Cunha (2023)
Diffuse large B-cell lymphoma (DLBCL) is the most common lymphoma in adults, often with aggressive behavior and representing a clinically and genetically heterogeneous disease. Hence, it has been proposed to classify DLBCL in two subsets by the cell‐of‐origin into germinal center (GC) and non-germinal center (nGC) subtypes, with apparent distinct pathogenic pathways and differences with respect to clinical course. Additional biomarkers, such as MYC and BCL2 expression and chromosomic translocations involving MYC, BCL2 and BCL6, have been given attention as DLBCL prognostic stratification. Alterations involving TP53, an important tumor suppressor gene, and EZH2, which codifies a polycomb repressive complex 2 (PRC2) subunit and acts as a methyltransferase, seem to be associated to DLBCL pathogenesis, but their clinical impact is not well understood. On the other hand, different microRNA expression patterns, such as miR-125b and miR-155b, are described as key influencers on DLBCL biological behavior, however their association with the aforementioned genes are little reported. Another relevant aspect regarding these tumors is the presence of Epstein-Barr Virus (EBV), which also seem to imply on distinct prognostic patterns depending on the cell-of-origin classification. The aim of this study was to evaluate the pathogenetic and prognostic importance of MYC, BCL2 and BCL6 translocations, BCL2, MYC, TP53 and EZH2 protein expression, miR-125b and miR-155b expression profile and the presence of EBV in a series of DLBCL considering the cell-of-origin classification. Chromosomic rearrangements were carried out by fluorescent in situ hybridization (FISH), protein expressions by immunohistochemistry and microRNA detection, as well as the presence of EBV, by in situ hybridization, with special strategies. Among 139 DBCL cases, the GC subtype was slightly more frequent than the nGC (53.9% and 46.1%, respectively). In a first approach, EZH2 positivity was associated to MYC and TP53 expression (p=0.0002 and p=0.0000, respectively) and to high proliferative index (Ki-67>70%, p=0.0082). The nGC DLBCL presented the associations observed in the general sample; however, only TP53 immunodetection showed associations to EZH2 expression in the GC subtype. When we analyzed the microRNAs, miR-125b detection was positively correlated to the Ki-67 index (p= 0.035) in the nGC. Considering the GC subgroup, the percentage of miR-125b positive cells was also correlated to both MYC and MYC/BCL2 double expression (p= 0.047 and p= 0.049, respectively). When it comes to the clinical aspects, in the nGC patients, miR-155b percentage and intensity, as well as Allred score, were positively correlated to disease progression (p= 0.038, p=0.057 and p= 0.039, respectively). In a multivariate analysis, GC phenotype was a significant independent factor associated with higher overall survival (p=0.007) and, considering the nCG group, although not significant, the expression of TP53, miR-125b and miR-155b showed statistics trends to be regarded as potentials prognostic biomarkers in these tumors. Taking in consideration EBV, 7.9% of cases were EBV(+)-DLBCL. Although the number of EBV (+) cases is not high, most of the tumors (72.7%) had a high proliferative index (Ki-67>70%) independently on being GC or nGC subtype. miR-125b was detected in almost all of these cases, and conversely, only two cases were miR155b positive. It is noteworthy that BCL2 expression was observed in most cases, although BCL2 translocation was a rare event, being detected in only two cases. Similarly, MYC expression and MYC translocation were rarely observed, and TP53, on the other hand, was commonly expressed (45.4%). In conclusion, the significant associations among EZH2, MYC and TP53, with different patterns depending on cell-of-origin classification, indicate potential pathogenetic pathways in these subtypes. miR-125b expression is related to MYC in nGC-DLBCL. In addition, TP53, miR-125b and miR-155b seem to represent potential prognostic factors in the nGC subtype.